南極昭和基地で観測された微気圧変動シグナルの長期トレンド - 石原, 吉明; 金尾, 政紀; 山本, 真行; 柿並, 義宏; 村山, 貴彦; 岡田, 和見; 戸田, 茂; 松島, 健; Ishihara, Yoshiaki; Kanao, Masaki; Yamamoto, Masa-yuki; Kakinami, Yoshihiro; et al. (2014)
conference object